A pilot study: effect of irisin on trabecular bone in a streptozotocin-induced animal model of type 1 diabetic osteopathy utilizing a micro-CT - Mohsin, Sahar; Brock, Fiona; Kaimala, Suneesh; Greenwood, Charlene; Sulaiman, Mohsin; Rogers, Keith; Adeghate, Ernest (PeerJ Publishing, 2023)
Background. Osteoporosis is a significant co-morbidity of type 1 diabetes mellitus (DM1) 41 leading to increased fracture risk. Exercise-induced hormone 'irisin' in low dosage has been 42 shown to have a beneficial effect on bone metabolism by increasing osteoblast differentiation 43 and reducing osteoclast maturation, and inhibiting apoptosis and inflammation. We investigated 44 the role of irisin in treating diabetic osteopathy by observing its effect on trabecular bone. 45 Methods. DM1 was induced by intraperitoneal injection of streptozotocin 60 mg/kg body 46 weight. Irisin in low dosage (5 μg twice a week for 6 weeks I/P) was injected into half of the 47 control and 4-week diabetic male Wistar rats. Animals were sacrificed six months after induction 48 of diabetes. The trabecular bone in the femoral head and neck was analyzed using a micro-CT 49 technique. Bone turnover markers were measured using ELISA, Western blot, and RT-PCR 50 techniques. 51 Results. It was found that DM1 deteriorates the trabecular bone microstructure by increasing 52 trabecular separation (Tb-Sp) and decreasing trabecular thickness (Tb-Th), bone volume fraction 53 (BV/TV), and bone mineral density (BMD). Irisin treatment positively affects bone quality by 54 increasing trabecular number p < 0.05 and improves the BMD, Tb-Sp, and BV/TV by 21-28%. 55 The deterioration in bone microarchitecture is mainly attributed to decreased bone formation 56 observed as low osteocalcin and high sclerostin levels in diabetic bone samples p < 0.001. The 57 irisin treatment significantly suppressed the serum and bone sclerostin levels p < 0.001, 58 increased the serum CTX1 levels p < 0.05, and also showed non-significant improvement in 59 osteocalcin levels. 60 Conclusions. This is the first pilot study to our knowledge that shows that a low dose of irisin 61 marginally improves the trabecular bone in DM1 and is an effective peptide in reducing 62 sclerostin levels.
Keywords: Diabetes; Irisin; Streptozotocin; Trabecular bone; Micro-CT; Osteoporosis; Diabetic osteopathy; Sclerostin; Type 1 diabetes